COMPLEX VIEW OF THE ERUPTION OF THE PERMANENT TEETH - Boyan Kirilov (Peytchinski Publishing, 2023)
The eruption of the permanent teeth is one of the main features used to determin the biological maturity of an individual. The present literature review shows a correlation between studies carried out in different years and countries for the factors influencing the erupting of teeth. Data regarding the role of social factors, sex, diet, height, weight, Body Mass Index (BMI), factors in pregnancy, diseases atyoung age, hereditary elements and genetics is analyzed. Tooth eruption in the context of secular trends is observed and attention is paid to the Bulgarian contribution to the study of this topic. The conclusion presents the importance of collaboration between different specialists in the preparation and execution of complex treatment plans.